Of ice and water: Quaternary fluvial response to glacial forcing. (15th June 2017) - Cordier, Stéphane; Adamson, Kathryn; Delmas, Magali; Calvet, Marc; Harmand, Dominique
Abstract: Much research, especially within the framework of the Fluvial Archives Group, has focused on river response to climate change in mid-latitude non-glaciated areas, but research into the relationships between Quaternary glacial and fluvial dynamics remains sparse. Understanding glacial–fluvial interactions is important because glaciers are able to influence river behaviour significantly, especially during glacial and deglacial periods: (1) when they are located downstream of a pre-existing fluvial system and disrupt its activity, leading to hydrographical, hydrosedimentary and isostatic adjustments, and (2) when they are located upstream, which is a common scenario in mid-latitude mountains that were glaciated during Pleistocene cold periods. In these instances, glaciers are major water and sediment sources. Their role is particularly significant during deglaciation, when meltwater transfer towards the fluvial system is greatly increased while downstream sediment evacuation is influenced by changes to glacial–fluvial connectivity and basin-wide sediment storage. This means that discharge and sediment flux do not always respond simultaneously, which can lead to complex fluvial behaviour involving proglacial erosion and sedimentation and longer-term paraglacial reworking. These processes may vary spatially and temporally according to the position relative to the ice margin (ice-proximal versus ice-distal). With a focus on the catchments of Europe, this paper aims to review our understanding of glacial impacts on riversystem behaviour. We examine the methods used to unravel fluvial response to 'glacial forcing', and propose a synthesis of the behaviour of glacially-fed rivers, opening perspectives for further research. Highlights: The influence of glaciers on fluvial systems is reviewed. A distinction between 'glacially-disrupted' (downstream control) and 'glacially-fed' (upstream control) rivers is highlighted. Downstream control influences river systems in terms of hydrography, hydro-sedimentary flows and isostacy. Upstream control mainly influences hydro-sedimentary flows. A model of behaviour of glacially-fed rivers is proposed, based on research undertaken especially in Europe.